Trauma echoes: factors associated with peritraumatic distress and anxiety five days following Iranian missile attack on Israel - Boaz M. Ben-David; Tchelet E. Bressler; Lia Ring; Ortal Shimon-Raz; Yuval Palgi (European Journal of Psychotraumatology)
Introduction: On 13–14 April 2024, Iran launched ∼300 drones and missiles at Israel, in an unprecedented attack. As most studies examine the effects of trauma months or years later, less is known about its effects days later. To fill this gap, this study gauged the population response, five days after the attack. Specifically, we examined the prevalence and factors associated with two precursors for later development of PTSD, peritraumatic distress (PD) and generalized anxiety disorder (GAD).Methods: Five-hundred and fifty-three participants (Mage = 57.51, SD = 13.67 years, range [30–90], 48.3% females) reported their distal and proximal exposure to traumatic events, probable PTSD due to Israel-Hamas-War, sleeping troubles, and media information consumption during the event.Results: Logistic regressions indicated that, after adjusting for demographics, clinical levels of PD and GAD (respectively, using the accepted cutoffs) were significantly linked to probable PTSD due to the Israel-Hamas War (PD:OR = 4.066, 95%CI: 2.236–7.393, p < .001; GAD:OR = 2.397, 95%CI: 1.285–4.471, p = .006), sleeping troubles (PD:OR = 1.248, 95%CI: 1.186–1.314, p < .001; GAD:OR = 1.325, 95%CI: 1.242–1.413, p < .001) and media consumption (PD:OR = 1.442, 95%CI:1.17–1.777, p = .001; GAD:OR = 1.515, 95%CI: 1.144–2.007, p = .004), but not to previous trauma (life-long exposure or Israel-Hamas war).Discussion: Results suggest that previous psychopathology, stress-related reactions (sleeping) and actions (media consumption), rather than previous exposures to traumatic events are the primary indices related to PD and GAD in the first days after exposure to war-related traumatic events. Findings highlight the importance of early detection of reactions and symptoms following trauma exposure. The main limitation of the study is its cross-sectional design. Future longitudinal studies are needed to understand the developmental trajectory of these effects.